HUBUNGAN RESPONSE TIME PETUGAS PENDAFTARAN DENGAN KEPUASAN PASIEN DI TEMPAT PENDAFTARAN PASIEN RAWAT JALAN PUSKESMAS BARENG KOTA MALANG - Maria Angela Agustina (Health Care Media, 2023)
Public health care plays an important role in treating patients according to operating standards (SOP) that are operating in the public center and noting the level of quality of health care. The quality of good health care from a center can be judged on a patient's level of satisfaction. One indicator of early satisfaction for a patient is the waiting time at the registration site. The waiting time of the patient or the so-called response time is the period required to complete the full ministerial process of any kind of service. The purpose of this research is to analyze the relation of response time the registrant has to the patient's satisfaction at an inpatient registration of Puskesmas Bareng, Malang. The study was carried out from February to June 2023. As for sample extraction techniques in this study using sampling techniques. The study used the chi-square test and found results of p value 0.05 so that it could be concluded that there is a significant connection between the response time the registration officer to the patient's satisfaction at PUSKESMAS Bareng, Malang. Keyword: Response time, satisfaction, outpatient